Implementation Of Character Strengthening In Boarding School Students - Hanafiah Hanafiah; Arin Tentrem Mawati; Opan Arifudin (Lafadz Jaya Publisher, 2022)
Today the attitudes and behavior of the younger generation are starting to ignore the noble values ​​that have long been a national tradition and run in everyday life, such as honesty, politeness, togetherness, and religious values. The purpose of this study was to determine the Implementation of Character Strengthening in Boarding School Students. This study uses a qualitative approach with descriptive methods. The results of this study indicate that the implementation of learning activities at boarding schools combined with character building has a great impact on improving student character. Learning at boarding school applies general learning and Islamic education consequently. So, every student must have an honest attitude and all these activities are also reflected in the daily life of students in the dormitory.